2013
DOI: 10.3892/br.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

The S protein of hepatitis B virus promotes collagen type I expression in hepatic stellate cells by virtue of hepatocytes

Abstract: Abstract. This study was conducted in order to investigate whether hepatitis B surface S protein (HBs) was able to directly or indirectly promote the proliferation and expression of collagen type I (Col I) and α-smooth muscle actin (α-SMA) in hepatic stellate cells (HSCs). The LX-2 human cell line and the HepG2 human hepatocellular carcinoma cell line were employed as HSCs and as hepatocytes, respectively. Recombinant HBs was added to the LX-2 cells for 48 h and the cell proliferation was assessed by the MTT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…HBV directly promotes collagen type I expression in LX-2 cells [ 40 ]. The HBV S antigen (HBsAg) also directly affects the proliferation of HSCs and promotes collagen type I expression in LX-2 cells [ 41 , 42 ]. It was also reported that HBeAg directly activated HSCs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBV directly promotes collagen type I expression in LX-2 cells [ 40 ]. The HBV S antigen (HBsAg) also directly affects the proliferation of HSCs and promotes collagen type I expression in LX-2 cells [ 41 , 42 ]. It was also reported that HBeAg directly activated HSCs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic stellate cell (HSC) activation is a central event in liver fibrosis [ 9 , 10 ]. Although recent investigations have suggested that direct activation of HSCs mediated by HBV is associated with liver fibrosis [ 11 ], whether HBV can directly infect HSCs has not been fully confirmed. After HBV-induced liver injury, hepatocytes release a variety of soluble inflammation-related molecules, such as TGF-β and CTGF [ 12 , 13 ], to accelerate HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HBV particles from HepG2.2.15 cells can transiently infect HSCs, specifically LX-2 cells, leading to HBsAg and HBcAg production in the cytoplasm of virus-infected HSCs and affecting their proliferation and expression of COL1A1 [ 11 ]. The viral particles derived from HepG2.2.15 cells also upregulate the expression of α-SMA, PDGF-B, and PDGFR-β, as well as enhance the phosphorylation of PDGFR-β, in HSCs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations